Cyber crime and cyber terrorism investigator's handbook - Akhgar, Babak; Bosco, Francesca; Staniforth, Andrew (Syngress, 2014)
Cyber Crime and Cyber Terrorism Investigator's Handbook is a vital tool in the arsenal of today's computer programmers, students, and investigators. As computer networks become ubiquitous throughout the world, cyber crime, cyber terrorism, and cyber war have become some of the most concerning topics in today's security landscape.